Prevalence of anxiety and depressive symptoms and impact on self-management among adults with chronic conditions in Chicago, Illinois, USA, during the COVID-19 pandemic: a cross-sectional survey. Issue 1 (7th January 2022) - Lovett, Rebecca M; Opsasnick, Lauren; Russell, Andrea; Yoon, Esther; Weiner-Light, Sophia; Serper, Marina; Cooper Bailey, Stacy; Wolf, Michael S
Abstract : Objectives: To examine the prevalence of mental health symptoms during the first surge of COVID-19 in the USA, and their associations with COVID-19-related emotional distress, health self-management and healthcare utilisation. Design: Cross-sectional analysis of wave 3 (1–22 May 2020) survey data from the ongoing Chicago COVID-19 Comorbidities (C3) study. Setting: Seven academic and community health centres in Chicago, Illinois. Participants: 565 adults aged 23–88 with one or more chronic conditions completing at least one prior C3 study wave. Primary and secondary outcome measures: Clinically relevant anxiety and depressive symptoms as measured using Patient-Reported Outcomes Measurement Information System short forms. Self-reported emotional and health-related responses to COVID-19 were measured through a combination of single-item questions and validated measures. Results: Rates of anxiety and depressive symptoms were 14% (81/563) and 15% (84/563), respectively. Anxiety and depressive symptoms were then each separately associated with greater worry about contracting COVID-19 (relative risk (RR) 2.32, 95% CI 1.52 to 3.53; RR 1.67, 95% CI 1.10 to 2.54), greater stress (RR 4.93, 95% CI 3.20 to 7.59; RR 3.01, 95% CI 1.96 to 4.61) and loneliness (RR 3.82, 95% CI 2.21 to 6.60; RR 5.37, 95% CI 3.21 to 8.98), greater avoidance of the doctor (RR 1.62, 95% CI 1.06 to 2.49; RR 1.54, 95% CI 1.00 to 2.36) and difficulty managing health (least square means (LS Means) 6.09, 95% CI 5.25 to 6.92 vs 4.23, 95% CI 3.70 to 4.75; LS Means 5.85, 95% CI 5.04 to 6.65 vs 4.22, 95% CI 3.70 to 4.75) and medications (LS Means 3.71, 95% CI 2.98 to 4.43 vs 2.47, 95% CI 2.02 to 2.92) due to the pandemic. Conclusions: Identifying and addressing mental health concerns may be an important factor to consider in COVID-19 prevention and management among high-risk medical populations.